STUDI KASUS PENERAPAN EVIDENCE BASED NURSING (EBN) TERAPI RELAKSASI OTOT PROGRESIF (ROP) DALAM MENGATASI KEJENUHAN KERJA PERAWAT DI RUANG ICU - Heni Lestari, (2022)
CASE STUDY : THE APPLICATION OF EVIDENCE BASED NURSING (EBN) PROGRESSIVE MUSCLE RELAXATION (ROP) THERAPY IN OVERCOMING NURSE BURNOUT IN THE ICU Heni Lestari Abstract The role of nurses in the ICU is different from nurses in other rooms where nurses must have skills and knowledge. The high workload of nurses requires nurses to work under stressful conditions optimally, resulting in stress and fatigue. It was found that from 8 nurses serving in the ICU, 5 nurses (62.5%) were in the high burnout category and 3 nurses (37.5%) were in the low burnout category. Therefore, the authors aim to manage work saturation for nurses by applying progressive muscle relaxation techniques. The case study begins by conducting a pre-test using the Burnout Measuring Instrument Questionnaire with the Maslach Burnout Inventory (MBI), after the burnout data is collected, the authors then carry out the implementation of the nursing interventions that have been made. Therapy is given for 3 consecutive days, each session of 20 minutes with 14 relaxation movements that can relax the body. After doing the post test using the same questionnaire to find out the description of burnout for nurses after being given therapy. The results of the post test showed a decrease in the level of burnout after being given therapy to 5 nurses. The author hopes that Progressive Muscle Relaxation Therapy can continue to be implemented for nurses to overcome burnout so that nurses' work performance does not decrease. Keywords : Burn Out, Nurse, Progressive Muscle Relaxation